Comparison of Rod-Airfoil Noise Calculation between Large Eddy Simulation (LES) and Detached-Eddy Simulation (DES) - Samion, Siti Ruhliah Lizarose; Mat Ali, Mohamed Sukri (CFD Letters, 2021)
Airfoil Leading Edge noise is generated due to impingement of turbulent structures on the airfoil surface. The rod-airfoil configuration is a benchmark configuration for the Leading edge noise and their noise calculation by computer simulation has peen progressively investigated to acceptable compare with the experiment. This paper presents the noise results finding between two distinct simulation models and their comparison with the experimental results. The two simulation models are Large-eddy simulation (LES) and the Delayed Detached-Eddy simulation (DDES). The DES can provide good noise results with the correct number of meshing grids with shorter timespan if compared to the LES. This study proposes to use DDES results for further rod-airfoil noise analysis.